Electronic origins of structural distortions in post-transition metal oxides: experimental and theoretical evidence for a revision of the lone pair model - Payne, D; Egdell, R; Walsh, A; Watson, G; Guo, J; Glans, P; Learmonth, T; Smith, K (American Physical Society, 2006)
Structural distortions in post-transition metal oxides are often explained in terms of the influence of s p hybrid "lone pairs". Evidence is presented here showing that this model must be revised. The electronic structures of prototypically distorted α-PbO and α-Bi2O3 have been measured by high-resolution x-ray photoemission and soft x-ray emission spectroscopies. In contrast with the expectations of the lone pair model, a high density of metal 6s states is observed at the bottom of the valence band. The measurements are consistent with the results of density functional theory calculations.